Increased of Spiritual Attitudes and Social Attitudes Through the Integration Model of Science and Islam at the Madrasah Aliyah level - Dharmawan, Muhammad Luthfi; Padil, Moh.; Mustikawan, Alfin (Proceeding of International Conference on Islamic Education (ICIED); Vol 9 No 1 (2024): Proceeding of International Conference on Islamic Education (ICIED), 2024)
The purpose of this study is to identify the integration model of science and Islam in improving spiritual attitudes and social attitudes in MA al-Islam Jamsaren Surakarta. This study uses a mix method with a type of field research . The object of the chosen research is MA Al-Islam Jamsaren Surakarta. The design of the mix method used is sequential exploratory . The techniques used in data collection consist of observations, interviews and, documentation for qualitative and questionnaires for quantitative data. In selecting samples, the researcher used the purposive sampling technique on the qualitative method and random sampling on the quantitative data using the Slovin formula. In data analysis, the stages of data reduction were used on qualitative data and percentage analysis was used to determine the impact of integration on the improvement of spiritual-social attitudes. The results of this study show that the model of integration of science and Islam is based on several philosophical and historical reasons, namely how the position of the Quran and Hadith as a source of knowledge then emits various branches of other disciplines as a form of scientific interpretation. The integration of science and Islam in this madrasah has a good enough impact on improving students' spiritual attitudes and social attitudes. This is shown in the results of the answers of 100 students the improvement of spiritual attitudes and social attitudes is very good with the figures for the spiritual indicators of agreeing and strongly agreeing 85.3%, while social attitudes are 81.2%.